Leadership Recklessness and Resource Wastefulness: Reflections on Two Decades of Democracy in Nigeria - Feyisara , Olaitan Eunice; Arum, Ifeyinwa (Kashere Journal of Politics and International Relations, 2025)
Over the past two decades, Nigeria has undergone significant political transitions, marking its evolution into a democratic state. However, amidst these advancements, the nation grapples with a recurring dilemma: leadership recklessness and resource wastefulness. This paper examines the nexus between democratic governance and the persistent challenges of Nigeria’s mismanagement and squandering of resources. Drawing on an extensive literature review and empirical evidence, this paper explores the historical context and contemporary manifestations of leadership recklessness, characterised by corruption, inefficiency, and lack of accountability among public officials. Additionally, it investigates the systemic flaws and structural deficiencies within Nigeria’s governance framework that perpetuate resource wastefulness, hindering the nation’s socio-economic progress and development. Through critical analysis and comparative perspectives, this paper offers insights into the underlying factors fuelling leadership recklessness and resource misallocation, including political patronage, institutional weaknesses, and weak regulatory mechanisms. Furthermore, it assesses the implications of these challenges on Nigeria’s democracy, governance effectiveness, and prospects for sustainable development. Finally, the paper proposes policy recommendations and interventions to foster transparency, accountability, and responsible leadership to mitigate the adverse effects of recklessness and wastefulness, thus steering Nigeria towards inclusive growth and prosperity.